Navigating ethics: An investigation into the representation of Indigenous knowledges and subjectivities - Wright, Jacqueline Jane (Curtin University, 2008)
This thesis consists of two parts; a creative piece called The Telling and a critical essay which investigates the representation of Indigenous knowledges and subjectivities by non-Indigenous writers. In different ways, the novel and the exegesis attempt to tackle the problematic engagement which can ensue between Indigenous and non-Indigenous cultures regarding issues of representation and, as a whole, the thesis aims to make a contribution to understanding the negotiation process involved in issues of representation. Two main protagonists drive the plot of The Telling; a garbage man and a postgraduate university student. Interleaved between these two main storylines are a series of fictionalised oral history transcripts. In the process of conducting research to complete her degree, Annie Fletcher gets drawn into a mystery surrounding the disappearance of a young girl in a remote community in the northwest of the country. Annie uses her position as a researcher to collect stories and unravel a web of deception and intrigue. This leads her to a remarkable truth with ethical implications which has her questioning the basis of much she has taken for granted. The Telling is set in the landscape of remote north western Australia and represents a complex tapestry of people’s lives, disparate cultures, history, current politics and social upheaval.Navigating Ethics: An Investigation into the Representation of Indigenous Knowledges and Subjectivities takes the thematic strands pursued by the novel in order to examine the implications of non-Indigenous efforts to represent the Indigenous, in an Australian context, and investigate how this shapes the writing/research process. This exegesis explores the intersections between ethics, politics and storytelling as they enfold into each other and within the larger domains of culture. It examines the documentation of Indigenous knowledges and subjectivities by non-Indigenous researchers and writers with a view to providing ethical insight into the current climate of writer accountability. In doing so, it illustrates how the location and positionality of the speaker/author/narrator impacts on those being spoken for and spoken about. In addition, the nature of the problematic engagement between the Australian Indigenous community and non- Indigenous writers and researchers involved in the representation of Indigeneity is explored.